Silicon carbide ceramic tube connecting piece with hydrothermal corrosion-resistant and high-strength sealing joint and preparation method of silicon carbide ceramic tube connecting piece

By using welding technology combining AYMCS glass solder system and NITE phase powder, the welding problem of silicon carbide ceramic pipes is solved, and high-strength sealing and hydrothermal corrosion resistance are improved to ensure that the joints are still effective under high temperature and harsh conditions.

CN119797954APending Publication Date: 2025-04-11GUANGDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411971738.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The welding technology of existing silicon carbide ceramic tubes is difficult to achieve high strength and airtightness, and at the same time, it lacks high-temperature hydrothermal corrosion resistance, resulting in failure of the joints under harsh working conditions.

Method used

AYMCS glass solder system is used as a sintering aid, combined with NITE phase powder, and a connection pressure is applied under a protective atmosphere by discharge plasma sintering technology to prepare a silicon carbide ceramic tube connector with high-strength sealing joint.

Benefits of technology

The silicon carbide ceramic tube connectors have maintained high mechanical strength at 800℃, and significantly improved corrosion resistance under hydrothermal corrosion conditions of 360℃ to ensure the airtightness and strength of the joints.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797954A_ABST
    Figure CN119797954A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of ceramic connection, and discloses a silicon carbide ceramic pipe connecting piece with a hydrothermal corrosion-resistant and high-strength sealing joint and a preparation method of the silicon carbide ceramic pipe connecting piece. According to the connecting piece, the end face of the machining end with the inner taper angle end plug is coated with NITE phase powder slurry, the end plug coated with the NITE phase powder and a silicon carbide ceramic tube are assembled, then glass solder is loaded, oscillation is conducted, the glass solder is fully filled, and a piece to be connected is obtained; the glass solder is prepared by mixing Al2O3, Y2O3, MgO, CaO and SiO2, carrying out water quenching at 1600-1650 DEG C, and carrying out ball milling and drying; the NITE phase powder is SiC and a glass solder; and under the protective atmosphere, the pressure of 40-60 MPa is applied to a to-be-connected piece, and spark plasma sintering is conducted at the temperature of 1500-1600 DEG C, so that the composite material is obtained. The sealing joint in the connecting piece has high strength, good corrosion resistance and good sealing performance, and still keeps high mechanical strength at the temperature of 800 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ceramic connection, and in particular, relates to a silicon carbide ceramic pipe connector with hydrothermal corrosion resistance and high-strength sealing joints and a preparation method thereof. Background Art

[0002] Silicon carbide (SiC) is a strong covalent bond material with excellent chemical and mechanical properties. It is widely used in advanced research fields such as aviation, aerospace, and nuclear energy. The 2011 Fukushima nuclear crisis exposed the serious hidden dangers of zirconium alloys in the state of loss of coolant accidents. In order to improve the safety and stability of nuclear power, scholars proposed the concept of accident tolerant fuel (ATF). Silicon carbide ceramic materials have excellent properties such as resistance to high-temperature oxidation, high-temperature creep, corrosion resistance, wear resistance, good thermal shock resistance, and resistance to neutron irradiation. They are considered to be candidate materials for accident-resistant fuel cladding of light water reactors. At a high temperature of 1000°C, the cladding tube made of silicon carbide ceramic materials can still maintain high mechanical properties, and its reaction rate with water vapor is three orders of magnitude lower than the reaction rate of zirconium alloys with water vapor. In actual application, the silicon carbide cladding tube needs to be sealed to prevent the external high-temperature and high-pressure water from eroding the fibers of the cladding tube and the nuclear fuel pellets inside. At present, the welding and packaging problem of silicon carbide-based cladding tubes has not been completely solved. Silicon carbide ceramics have a high melting point and a low self-diffusion coefficient, making it difficult to connect them through melting welding like metal materials. Therefore, a reliable welding method is needed to encapsulate silicon carbide to ensure that it still has excellent performance under harsh working conditions. At the same time, the development of silicon carbide ceramic connection technology can decompose complex components into simple components for connection, which can greatly reduce production costs, facilitate industrial production, and is of great significance to the development of the national industry.

[0003] At present, the welding technologies of silicon carbide ceramics include: diffusion welding, reaction welding, metal brazing, nano-transient eutectic phase connection, precursor method connection and glass connection, etc. In the field of silicon carbide nuclear cladding, the silicon carbide cladding joint is required to have a stable and high connection strength, good air tightness, and the weld can resist high-temperature hydrothermal corrosion. Glass connection is a connection method to obtain a high-sealing performance joint. The joint has a moderate connection strength, but the currently disclosed glass solders are not resistant to high-temperature hydrothermal corrosion. The nano-transient eutectic phase connection with silicon carbide as the main phase is convenient and fast, but it requires pressurized connection. Due to the structural limitations of silicon carbide ceramic tubes, the embedded tube plug structure reported in the literature (such as Figure 1 (a) Joint and flat pipe plug structure ( Figure 1(b)) Joints have problems of poor air tightness and low ejection strength. Nano-transient eutectic phase SiC ceramics show better corrosion resistance than glass, but their corrosion rate is still an order of magnitude higher than that of high-purity CVD-SiC ceramics. The essence of nano-transient eutectic phase connection is liquid phase sintering, and the grains are bonded to each other through sintering aids. Its corrosion resistance depends to a large extent on the corrosion resistance of the sintering aids. However, most of the sintering aid systems are developed based on promoting densification, and the aid systems developed for improving hydrothermal corrosion performance are scarce. To date, there is no data report on nano-transient eutectic phase joints that meet the hydrothermal corrosion assessment of a refueling cycle (18 months). Summary of the invention

[0004] In order to solve the above-mentioned shortcomings and deficiencies of the nano-transient eutectic phase connection of the embedded tube plug structure in the prior art, such as low strength and airtightness, poor corrosion resistance of the commonly used sintering aid connection layer, and traditional glass solder connection can provide high strength and airtightness but is not resistant to high-temperature hydrothermal corrosion, resulting in joint failure, the primary purpose of the present invention is to provide a silicon carbide ceramic tube connector with hydrothermal corrosion resistance and high-strength sealing joint. The sealing joint in the connector has high strength, good corrosion resistance and good sealing performance, and still maintains high mechanical strength at 800°C.

[0005] Another object of the present invention is to provide a method for preparing the above-mentioned silicon carbide ceramic pipe connector with water-heat corrosion resistance and high-strength sealing joint.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A silicon carbide ceramic tube connector with hydrothermal corrosion resistance and high-strength sealing joint, wherein the silicon carbide ceramic tube connector is formed by coating a NITE phase powder slurry on the end surface of a processed end with an inner cone angle end plug, assembling the end plug coated with the NITE phase powder with the silicon carbide ceramic tube, and then filling the glass solder and oscillating it to make it fully filled to obtain a connection piece; the glass solder is Al 2 O 3 , Y 2 O 3 , MgO, CaO and SiO 2 The NITE phase powder is a mixture of SiC and glass solder. The NITE phase powder is prepared by applying a connection pressure of 40 to 60 MPa to the parts to be connected under a protective atmosphere and performing spark plasma sintering at 1500 to 1600°C.

[0008] Preferably, the Al 2 O 3 , Y 2 O3 , MgO, CaO and SiO 2 The mass ratio of the SiC is (17-20):(4-6):(8-12):(7-10):(52-64); the particle size of the SiC is 30-120 nm, and the mass ratio of the SiC and the glass solder is (70-97):(3-30).

[0009] More preferably, the Al 2 O 3 , Y 2 O 3 , MgO, CaO and SiO 2 The mass ratio of the SiC is 18:5:11:9:57; the particle size of the SiC is 50 nm, and the mass ratio of the SiC to the glass solder is 95:5.

[0010] Preferably, the NITE phase slurry is a mixture of NITE phase powder and anhydrous ethanol, the mass ratio of NITE phase powder to anhydrous ethanol is (0.5-1): (10-10.5), and the mass of the coated NITE phase powder is 50-70 mg / cm 2 .

[0011] Preferably, the protective atmosphere is nitrogen, helium or argon.

[0012] Preferably, the thickness of the silicon carbide ceramic NITE phase powder connection layer in the silicon carbide ceramic tube connection piece is 15 to 20 μm, and the thickness of the glass connection layer is 60 to 80 μm; the helium leakage rate of the connection piece at room temperature is 0 to 9.9×10 -14 Pa·m 3 / s, the ejection strength is 64~66MPa; at 800℃, the helium leakage rate of the connector is 0~1.0×10 -13 Pa·m 3 / s, the ejection strength is 60~63MPa; at 360℃, 18MPa hydrothermal corrosion for 14 days, the corrosion weight loss rate is 5~9×10 -1 mg / cm 2 ·day, the helium leakage rate of the connector is 0~5.0×10 -13 Pa·m 3 / s, the connection strength is 58~61MPa.

[0013] Preferably, the semi-cone angle θ of the silicon carbide ceramic tube is 1 =1~5°, the height of the end plug is 7~9mm, and the semi-cone angle θ of the end surface at the bottom of the end plug 2 =40~60°, and the gap between the rear end plug and the silicon carbide ceramic cladding tube after assembly is 60~80μm.

[0014] The method for preparing the silicon carbide ceramic pipe connector with water-heat corrosion resistance and high-strength sealing joint comprises the following steps:

[0015] S1. Coat the end surface of the end plug with an inner cone angle with NITE phase powder slurry, assemble the end plug coated with NITE phase powder with the silicon carbide ceramic cladding tube, and then load glass solder into the silicon carbide ceramic tube with an inner cone angle, oscillate it to make it fully filled, and obtain the part to be connected; the glass solder is Al 2 O 3 , Y 2 O 3 , MgO, CaO and SiO 2 Mixing, heating to 1600-1650°C, keeping the temperature, water quenching, ball milling and drying to obtain the NITE phase powder; the NITE phase powder is a mixture of SiC and glass solder;

[0016] S2. Under a protective atmosphere, place the parts to be connected in a spark plasma sintering furnace, apply a connection pressure of 40 to 60 MPa, first heat up to 600 to 700 ° C, then heat up to 1500 to 1600 ° C for insulation, cool down to below 800 ° C and cool with the furnace to obtain silicon carbide ceramic pipe connectors with resistance to hydrothermal corrosion and high-strength sealing joints.

[0017] Preferably, the insulation time at 1600-1650° C. in step S1 is 30-120 min.

[0018] Preferably, in step S2, the heating rate to 600-700°C is 50-100°C / min, the heating rate to 1500-1600°C is 30-50°C / min, the insulation time is 10-30min, and the cooling rate is 100-200°C / min.

[0019] The AYMCS glass solder of the present invention is added to silicon carbide as a sintering aid, which can significantly reduce the sintering temperature of silicon carbide ceramics and improve the corrosion resistance. Since the AYMCS glass solder has a relatively low viscosity and good fluidity at high temperatures, it can fill the weld well during the connection process to ensure its sealing performance. The thermal expansion coefficient of the AYMCS glass solder is similar to that of the silicon carbide ceramic, and the interface bonding is good, thereby improving the joint strength.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The present invention provides a hydrothermal corrosion resistant glass solder system AYMCS (A = Al 2 O 3 , Y=Y 2 O 3, M=MgO, C=CaO, S=SiO 2 ), the solder system has excellent mechanical properties, moderate viscosity, excellent corrosion resistance, and its thermal expansion coefficient is similar to that of silicon carbide ceramics. The mechanical properties of the solder system are the ejection strength of the joint, the glass connection layer evenly fills the weld, and there are no cracks. It has a thermal expansion coefficient similar to that of silicon carbide ceramics, corrosion resistance, and the microstructure of the connection layer does not change much before and after corrosion. No connection layer is found to fall off or missing. Compared with traditional glass solders, this solder can improve the room temperature mechanical properties and high temperature mechanical properties of the joint, as well as its corrosion resistance and air tightness, and greatly improve the reliability of the joint connection.

[0022] 2. The present invention adds hydrothermal corrosion resistant glass solder to silicon carbide as a sintering aid. Since hydrothermal corrosion corrodes the silicon carbide block, the grain boundary is corroded first. There is a sintering aid at the grain boundary of liquid phase sintered silicon carbide, so the corrosion resistant sintering aid can improve the hydrothermal corrosion performance of the NITE phase connection. Prepare NITE phase powder coupling glass solder to connect SiC ceramic tubes, reduce the required welding temperature, significantly improve the joint air tightness and joint strength, and improve the corrosion resistance of the joint;

[0023] 3. The present invention uses two kinds of solders to connect the SiC ceramic tube plug, performs semi-conical angle processing on the end plug, and makes a chamfer at the end plug mouth to give the end plug an inclination, thereby ensuring the coaxiality of the tube plug, so that the tube plug fits without displacement, and the uniformity of the connection weld. The chamfer design on the top of the end plug is conducive to the filling of glass solder at high temperature, while ensuring that the solder only exists in the joint area, which is convenient for the subsequent filling of objects into the SiC ceramic tube. The end plug is designed to be T-shaped and a distance is reserved between the end plug and the SiC ceramic tube, which is used for glass solder that can be filled without pressure at high temperature. The end face of the T-shaped end plug provides support for the pressure of the nano transient eutectic phase powder (NITE). BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of the joint of the embedded pipe plug structure (a) and the flat pipe plug structure (b), refer to the standard "ASTM C1862-17".

[0025] Figure 2 The present invention is a schematic diagram of the silicon carbide ceramic cladding tube and end plug structure and their assembly (a), and a physical diagram of the silicon carbide ceramic cladding tube connector of the sealing joint (b).

[0026] Figure 3 This is an interface microstructure diagram of the silicon carbide ceramic cladding tube connector joint of Example 1.

[0027] Figure 4 This is an in-situ microstructure diagram of the silicon carbide ceramic cladding tube connector joint of Example 1 before and after 14 days of corrosion. DETAILED DESCRIPTION

[0028] The content of the present invention is further described below in conjunction with specific examples, but it should not be construed as limiting the present invention. If not specifically indicated, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0029] Example 1

[0030] 1. Add Al with a mass ratio of 18:5:11:9:57 2 O 3 , Y 2 O 3 , MgO, CaO and SiO 2 The powders are mixed, placed in a heat treatment furnace and heated to 1600°C for 60 minutes, water quenched to obtain glass, and then preliminarily ground and ball-milled to obtain glass solder.

[0031] 2. Mix SiC powder (particle size 50nm) and glass solder in a mass ratio of 95:5, ball mill and dry to obtain NITE phase powder;

[0032] 3. Place a silicon carbide ceramic cladding tube with an inner cone angle (outer diameter φ9.5mm, inner diameter φ7.9mm, length 20-22mm, half cone angle θ 1 =1.5°) and end plug (half cone angle θ 1 =1.5°, half cone angle θ of the end surface at the bottom of the end plug 2 =40°, the end plug height is 8mm), such as Figure 2 As shown, wash with ethanol and dry for later use;

[0033] 4. Mix NITE phase powder and anhydrous ethanol at a mass ratio of 1:10 for 10 minutes, and then coat the end surface of the processing end with 65 mg / cm 2 After the NITE phase powder is dried for 5 minutes, it is assembled with the silicon carbide ceramic cladding tube. The gap between the end plug and the silicon carbide ceramic cladding tube is 70μm. 0.15g of glass solder is filled into the silicon carbide ceramic cladding tube and shaken to make it fully and evenly filled to obtain the part to be connected;

[0034] 5. Load the parts to be connected into the mold, apply a connection pressure of 50 MPa, put them into a sintering furnace and heat them to 650 ° C at 100 ° C / min, introduce a protective atmosphere of Ar gas, then heat them to 1550 ° C at 50 ° C / min and keep them warm for 10 minutes, then cool them to 1000 ° C at 100 ° C / min, and finally cool them with the furnace to obtain a silicon carbide ceramic clad tube connector with hydrothermal corrosion resistance and high-strength sealing joints.

[0035] The thickness of the NITE connection layer of the sealing joint in the silicon carbide ceramic cladding tube connector of this embodiment is 15-20 μm, and the thickness of the glass connection layer is 70 μm; the helium leakage rate of the connector at room temperature is 9.9×10 -14 Pa·m 3 / s, the ejection strength is 66MPa; at 800℃, the helium leakage rate of the connector is 1.0×10 -13 Pa·m 3 / s, and the ejection strength is 63MPa; the weight loss rate of the silicon carbide ceramic cladding pipe connector after 14 days of hydrothermal corrosion at 360℃ and 18MPa is 5×10 -1 mg / cm 2 ·day, the helium leakage rate of the connector is 5.0×10 -13 Pa·m 3 / s, the connection strength is 61MPa.

[0036] Figure 2 The present invention is a schematic diagram of the silicon carbide ceramic cladding tube and end plug structure and their assembly (a), and a physical diagram of the silicon carbide ceramic cladding tube connector of the sealing joint (b). Figure 3 FIG. 1 is an interface microstructure diagram of the silicon carbide cladding tube connector of Example 1. Figure 3 It can be seen that the NITE phase connection layer and the glass connection layer are combined with the silicon carbide ceramic cladding tube without cracking and the weld filling is relatively complete. Figure 4 The in-situ microstructure diagram of the joint of the silicon carbide ceramic cladding tube connector of Example 1 before and after 14 days of corrosion. Among them, (a) is before the NITE phase connection layer is corroded, (b) is before the glass solder connection layer is corroded, (c) is after the NITE phase connection layer is corroded, and (d) is after the glass solder connection layer is corroded. Figure 4 It can be seen that the microstructure changes little before and after corrosion. After 14 days of water corrosion, the NITE phase connection layer and the glass connection layer largely maintain the state before water corrosion, and the NITE phase connection layer, the glass connection layer and the silicon carbide ceramic cladding tube are still well bonded.

[0037] Example 2

[0038] 1. Add Al with a mass ratio of 17:4:8:7:64 2 O 3 , Y 2 O 3 , MgO, CaO and SiO 2 The powders are mixed, placed in a heat treatment furnace and heated to 1650°C for 60 minutes, water quenched to obtain glass, and then preliminarily ground and ball-milled to obtain glass solder after drying;

[0039] 2. SiC powder (100 nm) and glass solder in a mass ratio of 9:1 were mixed and ball-milled and dried to obtain NITE phase powder;

[0040] 3. Place the silicon carbide ceramic cladding tube with an inner cone angle (half cone angle θ 1 =2°) and end plug (half cone angle θ 1 =2°, half cone angle θ of the end surface at the bottom of the end plug 2 =50°, the end plug height is 8mm), cleaned with ethanol, and dried for later use;

[0041] 4. Mix NITE phase powder and anhydrous ethanol at a mass ratio of 0.5:10 for 8 minutes, and then coat the end surface of the processing end with 55 mg / cm 2 The NITE phase powder was dried for 6 minutes and assembled with the silicon carbide ceramic cladding tube. The gap between the end plug and the silicon carbide ceramic cladding tube was 60 μm. 0.12 g of glass solder ( Figure 2 The white part in the middle is filled into the silicon carbide ceramic cladding tube, and vibrated to make it fully and evenly filled to obtain the parts to be connected;

[0042] 5. Load the parts to be connected into the mold, apply a connection pressure of 60MPa, put them into a sintering furnace and heat them to 600℃ at 80℃ / min, introduce a protective atmosphere of He gas, then heat them to 1500℃ at 30℃ / min and keep them warm for 20min, then cool them to 800℃ at 150℃ / min, and finally cool them with the furnace to obtain silicon carbide ceramic clad tube connectors with resistance to hydrothermal corrosion and high-strength sealing joints.

[0043] The thickness of the NITE connection layer of the sealing joint in the silicon carbide ceramic cladding tube connector of this embodiment is 10-15 μm, and the thickness of the glass connection layer is 60 μm; the helium leakage rate of the connector at room temperature is 1.0×10 -13 Pa·m 3 / s, the ejection strength is 64MPa; at 800℃, the helium leakage rate of the connector is 2.0×10 -13 Pa·m 3 / s, and the ejection strength is 61MPa; the weight loss rate of the silicon carbide ceramic cladding pipe connector after 14 days of hydrothermal corrosion at 360℃ and 18MPa is 7×10 -1 mg / cm 2 ·day, the helium leakage rate of the connector is 7.0×10 -13 Pa·m 3 / s, the connection strength is 59MPa.

[0044] Example 3

[0045] 1. Add Al in a mass ratio of 20:6:12:10:52 2 O3 , Y 2 O 3 , MgO, CaO and SiO 2 The powders are mixed, placed in a heat treatment furnace and heated to 1600°C for 100 minutes, then water quenched to obtain glass, which is then preliminarily ground and ball-milled to obtain glass solder after drying;

[0046] 2. Mix SiC powder (50nm) and glass solder in a ratio of 7:3 and then ball-mill and dry them to obtain NITE phase powder;

[0047] 3. Place the silicon carbide ceramic cladding tube with an inner cone angle (half cone angle θ 1 =4°) and end plug (half cone angle θ 1 =4°, half cone angle θ of the end surface at the bottom of the end plug 2 =45°, the end plug height is 7mm), cleaned with ethanol, and dried for later use;

[0048] 4. Mix NITE phase powder and ethanol at a mass ratio of 1:10 for 10 minutes, and apply 50 mg / cm 2 The NITE phase powder was left to air for 5 minutes and then assembled with the silicon carbide ceramic cladding tube. The gap between the end plug and the silicon carbide ceramic cladding tube was 65 μm. 0.08 g of glass solder was filled into the silicon carbide ceramic cladding tube and shaken to make it fully and evenly filled to obtain the parts to be connected.

[0049] 5. Load the parts to be connected into the mold, apply a connection pressure of 60MPa, put them into a sintering furnace and heat them to 700℃ at 70℃ / min, introduce protective atmosphere Ar gas, then heat them to 1600℃ at 50℃ / min and keep them warm for 30min, then cool them to 1000℃ at 200℃ / min, and finally cool them with the furnace to obtain silicon carbide ceramic clad tube connectors with hydrothermal corrosion resistance and high-strength sealing joints.

[0050] The thickness of the NITE connection layer of the sealing joint in the silicon carbide ceramic cladding tube connector of this embodiment is 5-10 μm, and the thickness of the glass connection layer is 65 μm; the helium leakage rate of the connector at room temperature is 1.5×10 -13 Pa·m 3 / s, the ejection strength is 65MPa; at 800℃, the helium leakage rate of the connector is 2.0×10 -13 Pa·m 3 / s, and the ejection strength is 62MPa; the weight loss rate of the silicon carbide ceramic cladding pipe connector after 14 days of hydrothermal corrosion at 360℃ and 18MPa is 9×10 -1 mg / cm 2 ·day, the helium leakage rate of the connector is 8.0×10 -13 Pa·m3 / s, the connection strength is 58MPa.

[0051] Example 4

[0052] 1. Al with a mass ratio of 17.5:5.5:10.5:10:56.5 2 O 3 , Y 2 O 3 , MgO, CaO and SiO 2 The powders are mixed, placed in a heat treatment furnace and heated to 1600°C for 90 minutes, then water quenched to obtain glass, which is then preliminarily ground and ball-milled to obtain glass solder after drying;

[0053] 2. Mix SiC powder (particle size 50nm) and glass solder in a mass ratio of 85:15, ball mill and dry to obtain NITE phase powder;

[0054] 3. Place the silicon carbide ceramic cladding tube with an inner cone angle (half cone angle θ 1 =5°) and end plug (half cone angle θ 1 =5°, half cone angle θ of the end surface at the bottom of the end plug 2 =60°, the end plug height is 7mm), cleaned with ethanol, and dried for later use;

[0055] 4. Mix NITE phase powder and anhydrous ethanol at a mass ratio of 0.5:10.5 for 12 minutes, and then apply 50 mg / cm 2 The NITE phase powder was left to air for 8 minutes and assembled with the silicon carbide ceramic cladding tube. The gap between the end plug and the silicon carbide ceramic cladding tube was 80 μm. 0.10 g of glass solder was filled into the silicon carbide cladding tube and shaken to make it fully and evenly filled to obtain the parts to be connected.

[0056] 5. Load the parts to be connected into the mold, apply a connection pressure of 45MPa, put them into a sintering furnace and heat them to 600℃ at 80℃ / min, introduce protective atmosphere Ar gas, then heat them to 1550℃ at 30℃ / min and keep them warm for 10min, then cool them to 1000℃ at 100℃ / min, and finally cool them with the furnace to obtain silicon carbide ceramic clad tube connectors with hydrothermal corrosion resistance and high-strength sealing joints.

[0057] The thickness of the NITE connection layer of the sealing joint in the silicon carbide ceramic cladding tube connector of this embodiment is 10-15 μm, and the thickness of the glass connection layer is 80 μm; the helium leakage rate of the connector at room temperature is 1.5×10 -13 Pa·m 3 / s, the ejection strength is 64MPa; at 800℃, the helium leakage rate of the connector is 4.0×10 -13 Pa·m3 / s, and the ejection strength is 60MPa; the obtained silicon carbide sealing joint is placed in an autoclave, and the weight loss rate of the joint of the silicon carbide ceramic cladding tube connector is 8×10 -1 mg / cm 2 ·day, the helium leakage rate of the connector is 8.0×10 -13 Pa·m 3 / s, the connection strength is 59MPa.

[0058] Example 5

[0059] 1. Add Al with a mass ratio of 19:6:9:8:58 2 O 3 , Y 2 O 3 , MgO, CaO and SiO 2 The powders are mixed, placed in a heat treatment furnace and heated to 1600°C for 60 minutes, then water quenched to obtain glass, which is initially ground and ball-milled and then dried to obtain glass solder;

[0060] 2. Mix SiC powder (particle size 50nm) and glass solder in a mass ratio of 3:1 and then ball-mill and dry to obtain NITE phase powder;

[0061] 3. Place the silicon carbide ceramic cladding tube with an inner cone angle (half cone angle θ 1 =4°) and end plug (half cone angle θ 1 =4°, half cone angle θ of the end surface at the bottom of the end plug 2 =60°, the end plug height is 8mm), cleaned with ethanol, and dried for later use;

[0062] 4. Mix NITE phase powder and anhydrous ethanol at a mass ratio of 1:10 for 10 minutes, and then apply 70 mg / cm 2 The powder was left to air for 6 minutes and assembled with the silicon carbide ceramic cladding tube. The gap between the end plug and the silicon carbide ceramic cladding tube was 70 μm. 0.15 g of glass solder was filled into the silicon carbide ceramic cladding tube and shaken to make it fully and evenly filled to obtain the parts to be connected.

[0063] 5. Load the parts to be connected into the mold, apply a connection pressure of 55 MPa, put them into a sintering furnace and heat them to 650 ° C at 100 ° C / min, introduce a protective atmosphere of He gas, then heat them to 1550 ° C at 50 ° C / min and keep them warm for 10 minutes, then cool them to 800 ° C at 100 ° C / min, and finally cool them with the furnace to obtain a silicon carbide ceramic clad tube connector with resistance to hydrothermal corrosion and high-strength sealing joints.

[0064] The thickness of the NITE connection layer of the sealing joint in the silicon carbide ceramic cladding tube connector of this embodiment is 15-20 μm, and the thickness of the glass connection layer is 70 μm; the helium leakage rate of the connector at room temperature is 4.0×10 -13 Pa·m 3 / s, the ejection strength is 64MPa; at 800℃, the helium leakage rate of the connector is 7.0×10 -13 Pa·m 3 / s, and the ejection strength is 61MPa; the weight loss rate of the silicon carbide ceramic cladding pipe connector after 14 days of hydrothermal corrosion at 360℃ and 18MPa is 6×10 -1 mg / cm 2 day, the helium leakage rate of the connector is 6.5×10 -13 Pa·m 3 / s, the connection strength is 59MPa.

[0065] The thickness of the silicon carbide ceramic NITE phase powder connecting layer in the silicon carbide ceramic tube connector of the present invention is 15 to 20 μm, and the thickness of the glass connecting layer is 60 to 80 μm; the helium leakage rate of the connector at room temperature is 0 to 9.9×10 -14 Pa·m 3 / s, the ejection strength is 64~66MPa; at 800℃, the helium leakage rate of the connector is 0~1.0×10 -13 Pa·m 3 / s, the ejection strength is 60~63MPa; at 360℃, 18MPa hydrothermal corrosion for 14 days, the corrosion weight loss rate is 5~9×10 -1 mg / cm 2 ·day, the helium leakage rate of the connector is 0~5.0×10 -13 Pa·m 3 / s, the connection strength is 58~61MPa.

[0066] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A silicon carbide ceramic pipe connector with water-heat corrosion resistance and high-strength sealing joint, characterized in that: The silicon carbide ceramic tube connector is prepared by coating NITE phase powder slurry on the end surface of a processed end with an end plug with an inner cone angle, assembling the end plug coated with NITE phase powder and the silicon carbide ceramic tube, and then filling glass solder and oscillating it to make it fully filled, thereby obtaining a part to be connected; the glass solder is prepared by mixing Al2O3, Y2O3, MgO, CaO and SiO2, water quenching at 1600-1650°C, ball milling and drying; the NITE phase powder is a mixture of SiC and glass solder; under a protective atmosphere, a connection pressure of 40-60MPa is applied to the part to be connected, and spark plasma sintering is performed at 1500-1600°C to obtain the part.

2. The silicon carbide ceramic pipe connector with water-heat corrosion resistance and high-strength sealing joint according to claim 1 is characterized in that: The mass ratio of Al2O3, Y2O3, MgO, CaO and SiO2 is (17-20):(4-6):(8-12):(7-10):(52-64); the particle size of SiC is 30-120 nm, and the mass ratio of SiC to glass solder is (70-97):(3-30).

3. The silicon carbide ceramic pipe connector with water-heat corrosion resistance and high-strength sealing joint according to claim 2 is characterized in that: The mass ratio of the Al2O3, Y2O3, MgO, CaO and SiO2 is 18:5:11:9:57; the particle size of the SiC is 50nm, and the mass ratio of the SiC to the glass solder is 95:

5.

4. The silicon carbide ceramic pipe connector with water-heat corrosion resistance and high-strength sealing joint according to claim 1, characterized in that: The NITE phase slurry is prepared by mixing NITE phase powder and anhydrous ethanol, wherein the mass ratio of NITE phase powder to anhydrous ethanol is (0.5-1):(10-10.5), and the mass of the coated NITE phase powder is 50-70 mg / cm 2 .

5. The silicon carbide ceramic pipe connector with water-heat corrosion resistance and high-strength sealing joint according to claim 1, characterized in that: The protective atmosphere is nitrogen, helium or argon.

6. The silicon carbide ceramic pipe connector with water-heat corrosion resistance and high-strength sealing joint according to claim 1, characterized in that: The thickness of the silicon carbide ceramic NITE phase powder connection layer in the silicon carbide ceramic tube connection piece is 15 to 20 μm, and the thickness of the glass connection layer is 60 to 80 μm; the helium leakage rate of the connection piece at room temperature is 0 to 9.9×10 -14 Pa·m 3 / s, the ejection strength is 64~66MPa; at 800℃, the helium leakage rate of the connector is 0~1.0×10 -13 Pa·m 3 / s, the ejection strength is 60~63MPa; at 360℃, 18MPa hydrothermal corrosion for 14 days, the corrosion weight loss rate is 5~9×10 -1 mg / cm 2 ·day, the helium leakage rate of the connector is 0~5.0×10 -13 Pa·m 3 / s, the connection strength is 58~61MPa.

7. The silicon carbide ceramic pipe connector with water-heat corrosion resistance and high-strength sealing joint according to claim 1, characterized in that: The semi-cone angle θ1 of the silicon carbide ceramic tube is 1-5°, the height of the end plug is 7-9 mm, the semi-cone angle θ2 of the end surface of the bottom of the end plug is 40-60°, and the gap between the rear end plug and the silicon carbide ceramic cladding tube after assembly is 60-80 μm.

8. The method for preparing a silicon carbide ceramic pipe connector having hydrothermal corrosion resistance and high-strength sealing joint according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Coating a NITE phase powder slurry on the end surface of the processed end with an inner cone angle end plug, assembling the end plug coated with NITE phase powder and the silicon carbide ceramic cladding tube, and then loading glass solder into the silicon carbide ceramic tube with an inner cone angle, oscillating to fully fill it, and obtaining a part to be connected; the glass solder is prepared by mixing Al2O3, Y2O3, MgO, CaO and SiO2, heating to 1600-1650°C, keeping the temperature, water quenching, ball milling and drying; the NITE phase powder is a mixture of SiC and glass solder; S2. Under a protective atmosphere, place the parts to be connected in a spark plasma sintering furnace, apply a connection pressure of 40 to 60 MPa, first heat up to 600 to 700 ° C, then heat up to 1500 to 1600 ° C for insulation, cool down to below 800 ° C and cool with the furnace to obtain silicon carbide ceramic pipe connectors with resistance to hydrothermal corrosion and high-strength sealing joints.

9. The method for preparing a silicon carbide ceramic pipe connector having hydrothermal corrosion resistance and high-strength sealing joint according to claim 8, characterized in that: The time of keeping the temperature at 1600-1650° C. in step S1 is 30-120 minutes.

10. The method for preparing a silicon carbide ceramic pipe connector having water-heat corrosion resistance and high-strength sealing joint according to claim 8, characterized in that: In step S2, the temperature is raised to 600-700°C at a rate of 50-100°C / min, the temperature is raised to 1500-1600°C at a rate of 30-50°C / min, the insulation time is 10-30 minutes, and the cooling rate is 100-200°C / min.